2013
DOI: 10.1136/bmj.f7139
|View full text |Cite
|
Sign up to set email alerts
|

The burden of air pollution on years of life lost in Beijing, China, 2004-08: retrospective regression analysis of daily deaths

Abstract: Objectives To better understand the burden of air pollution on deaths, we examined the effects of air pollutants on years of life lost (YLL) in Beijing, China.Design Retrospective regression analysis using daily time series.Setting 8 urban districts in Beijing, China.Participants 80 515 deaths (48 802 male, 31 713 female) recorded by the Beijing death classification system during 2004-08. Main outcome measuresAssociations between daily YLL and ambient air pollutants (particulate matter with aerodynamic diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
131
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(149 citation statements)
references
References 29 publications
13
131
3
2
Order By: Relevance
“…These findings are in line with the earlier report of Guo et al that showed the mortality risk was higher for older people than for those aged 65 years or younger. Interestingly, they also showed that the effect estimates of PM2.5 and PM10 on YLL were higher in women than men, with the opposite for SO 2 and NO 2 (Guo, Li et al, 2013). Similar findings have been reported on the relation between air pollution and premature elderly deaths in Moscow, Russia (Revich and Shaposhnikov, 2010;Shaposhnikov, Revich et al, 2014).…”
Section: The Social-economic Burden Of Pollution-induced Diseasessupporting
confidence: 72%
“…These findings are in line with the earlier report of Guo et al that showed the mortality risk was higher for older people than for those aged 65 years or younger. Interestingly, they also showed that the effect estimates of PM2.5 and PM10 on YLL were higher in women than men, with the opposite for SO 2 and NO 2 (Guo, Li et al, 2013). Similar findings have been reported on the relation between air pollution and premature elderly deaths in Moscow, Russia (Revich and Shaposhnikov, 2010;Shaposhnikov, Revich et al, 2014).…”
Section: The Social-economic Burden Of Pollution-induced Diseasessupporting
confidence: 72%
“…The adverse effect of long-term exposure to air pollution on type 2 diabetes risk is of much importance given the extraordinary confluence of high levels of air pollutants in urbanized environments, especially in rapidly urbanizing countries (23,25,26). Air pollution in China is a significant public health burden, especially in spring and winter (26,27). The pooled results of standardized risk estimates in the present meta-analysis suggest an obvious association of type 2 diabetes risk with long-term exposure to PM2.5 (Fig.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Accurately assessing PM 2.5 exposure is critical for estimating its health risks in such epidemiological studies. However, due to the limited number of ground monitors in China, previous studies generally ignored the spatial variation of PM 2.5 and assessed the ambient exposure uniformly using one monitor or averages of several monitors located within a city or a municipality [13][14][15][16], which causes exposure misclassification. Therefore, accurately estimating the fine-scale spatiotemporal variation of ground PM 2.5 may lay a foundation for future health-related studies of PM 2.5 in China.…”
Section: Introductionmentioning
confidence: 99%
“…Severe PM 2.5 pollution in China has attracted considerable public attention [10][11][12] and inspired numerous epidemiological studies to investigate the health effects of air pollution in China since 2013 [13][14][15][16][17][18]. Accurately assessing PM 2.5 exposure is critical for estimating its health risks in such epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%